K.Vita: a feasibility study of a blend of medium chain triglycerides to manage drug-resistant epilepsy. Issue 4 (23rd July 2021) - Schoeler, Natasha E; Orford, Michael; Vivekananda, Umesh; Simpson, Zoe; Van de Bor, Baheerathi; Smith, Hannah; Balestrini, Simona; Rutherford, Tricia; Brennan, Erika; McKenna, James; Lambert, Bridget; Barker, Tom; et al.
Abstract: This prospective open-label feasibility study aimed to evaluate acceptability, tolerability and compliance with dietary intervention with K.Vita, a medical food containing a unique ratio of decanoic acid to octanoic acid, in individuals with drug-resistant epilepsy. Adults and children aged 3–18 years with drug-resistant epilepsy took K.Vita daily whilst limiting high-refined sugar food and beverages. K.Vita was introduced incrementally with the aim of achieving ≤35% energy requirements for children or 240 ml for adults. Primary outcome measures were assessed by study completion, participant diary, acceptability questionnaire and K.Vita intake. Reduction in seizures or paroxysmal events was a secondary outcome. 23/35 (66%) children and 18/26 (69%) adults completed the study; completion rates were higher when K.Vita was introduced more gradually. Gastrointestinal disturbances were the primary reason for discontinuation, but symptoms were similar to those reported from ketogenic diets and incidence decreased over time. At least three-quarters of participants/caregivers reported favourably on sensory attributes of K.Vita, such as taste, texture and appearance, and ease of use. Adults achieved a median intake of 240 ml K.Vita, and children 120 ml (19% daily energy). Three children and one adult had ß-hydroxybutyrate >1 mmol/l. There was 50% (95% CI 39–61%) reduction in mean frequency of seizures/events. Reduction in seizures or paroxysmal events correlated significantly with blood concentrations of medium chain fatty acids (C10 and C8) but not ß-hydroxybutyrate. K.Vita was well accepted and tolerated. Side effects were mild and resolved with dietetic support. Individuals who completed the study complied with K.Vita and additional dietary modifications. Dietary intervention had a beneficial effect on frequency of seizures or paroxysmal events, despite absent or very low levels of ketosis. We suggest that K.Vita may be valuable to those with drug-resistant epilepsy, particularly those who cannot tolerate or do not have access to ketogenic diets, and may allow for more liberal dietary intake compared to ketogenic diets, with mechanisms of action perhaps unrelated to ketosis. Further studies of effectiveness of K.Vita are warranted. Abstract : See Auvin (https://doi.org/10.1093/braincomms/fcab234 ) for a scientific commentary on this article. Schoeler et al. report that K.Vita, a decanoic acid-rich medical food, was well-tolerated when introduced gradually and flexibly to individuals with epilepsy. Seizures or paroxysmal events reduced by 50% (95% CI 39–61%). Only 4/61 (7%) patients had ß-hydroxybutyrate levels >1 mmol/l. K.Vita may be valuable for individuals with drug-resistant epilepsy. Graphical Abstract: